Pengaruh Metode Drill Terhadap Hasil Belajar Matematika Siswa SMP Pertiwi Medan - Suvriadi Panggabean; Hari Sumardi (Universitas Muslim Nusantara Al Washliyah, 2018)
The purpose of this research was to determine The Effect Of Drill Method On The Student Result of Mathematics Learning In Pertiwi Junior High School Medan. This research was conducted in VIII-2 class and VIII-7 class Pertiwi Junior High School Medan. The method which is used in this research is quasi-experiment with pretest-posttest control group research design. The sample was determined by using purposive sample technique. This research sample are 50 students, with 25 students for experimental class and 25 students for control class. The instrument used in this reserach is a test instrument of multiple choices questions. Data from the test instrument’s result were analyzed quantitatively. Based on the analysis, the average score of students learning result in experiment class is 74,24, and 69,28 for the control class students. It is based on hypotesis test result by using t test to the posttest data with n = 25 and α = 5%. The result is the value of tcount = 2,80 while ttable = 2,20. It shows that t count > t table, so it can be concluded that there are effects of drill method to the student result of mathematics learning in algebra factorization. Keywords : Drill Method, Mathematics Learning Result